Eficiência técnica e inovatividade : um estudo em hospitais privados brasileiros - Saquetto, Thiago Chieppe (2012)
Innovation is currently considered one of the main contributing factors for competitive differentiation and organizational performance improvement. Investing in innovativeness, i.e.the great ability to promote innovation has been pointed as the way for the companies to achieve success in highly competitive markets. In the hospital business, enterprises have invested in innovation in order to enhance both the quality of their health services, as well the efficiency. However, given the multiple meanings of the terms innovation and innovativeness in the literature, there are still questions about the actual contributions of these factors for the enterprises performance. Especially in segments whose innovative dynamics is distinguished from others by their specific aspects, as in the hospital business. Thus this research aimed to clarify the influence of innovativeness in hospital performance. Therefore innovativeness was defined as a measure of the companys ability or propensity to innovate, both perceived by the organizations internal culture and the way of acting in the marketplace. This operation was achieved by compiling variables from two constructs of innovativeness: Organizational Innovativeness (IO) and Perceived Firm Innovativeness (PFI). Operational performance was defined as a measure of the efficiency, with which a private hospital enterprise uses the resources available to provide services, comparing to other private hospitals. By a comprehensive literature review, we identified non-financial variables often used in hospital researches, both domestic and international. This operation was achieved by using Data Envelopment Analysis (DEA) mathematical model. Based on a sample of 17 private hospitals, we found that the innovativeness perceived by hospital managers has an inverse relationship with the operational technical efficiency of hospital enterprises